New Insights Into the Backbone Phylogeny and Character Evolution of Corydalis (Papaveraceae) Based on Plastome Data - Xu, Xiaodong; Li, Xuexiu; Wang, Dong (Frontiers in Plant Science, 2022)
A robust backbone phylogeny is fundamental for developing a stable classification and instructive for further researches. However, it was still not available for Corydalis DC., a species-rich (> 500 species), ecologically and medically important, but taxonomically notoriously difficult genus. Here, we constructed backbone phylogeny and estimated the divergence of Corydalis based on plastome data from 39 Corydalis species (32 newly sequenced), which representing ca. 80% sections and series across this genus. Our phylogenetic analyses recovered six fully supported main clades (Ⅰ–Ⅵ), and provided full support for the majority lineages within Corydalis. Section Archaeocapnos was unexpectedly turned out to be sister to the rest subg. Corydalis s. l. (clades Ⅳ–Ⅵ), thus, treated as a distinct clade (clade Ⅲ) to render all the main clades monophyletic. Additionally, some unusual plastome structural rearrangements were constantly detected within Corydalis, and proved to be lineage-specific in this study, which in turn provided further support for our phylogeny. A segment containing five genes (trnV-UAC–rbcL) in the plastome LCS region was either normally located at downstream of ndhC gene in clade Ⅰ species, or translocated to downstream of atpH gene in clade Ⅱ species, or translocated to downstream of trnK-UUU gene in clad Ⅲ–Ⅵ species. The unique large inversion (ca. 50 kb) in the plastome LSC region of clade Ⅲ species, representing an intermediate stage of the above translocation in clade Ⅳ–Ⅵ, firmly supported clade Ⅲ as a distinct and early diverged clade within this large lineage (clad Ⅲ–Ⅵ). Our phylogeny contradicted substantially with the morphology-based taxonomy, rejected the treatment of tuberous species as an independent evolutionary group, and proved some commonly used diagnostic characters (e.g., root and rhizome) were results of convergent evolution, suggestive of unreliability in Corydalis. We dated the origin of crown Corydalis to the early Eocene (crown age 49.08 Ma), and revealed a possible explosive radiation around 25 Ma, coinciding with the drastic uplift of Qinghai-Tibetan Plateau in Oligocene and Miocene. This study provided the most reliable and robust backbone phylogeny of Corydalis to date, and shed some new insights on the evolution of Corydalis.